Unobtrusive measures: nonreactive research in the social sciences - Webb, Eugene; Campbell, Donald; Schwartz, Richard (New York : Rand McNally College Publishing Company, 1966)
Contents : Approximations to knowledge,phisical traces : erosion and acretion,archives 1: the running record,archives 2: the episodic and private record,simple observationcontrived observation : hidden hardware and control.
Incluye bibliografía Includes bibliographical references and index
Keywords: Familia - Matrimonio